Pengaruh Physical Evidence dan Gaya Hidup Terhadap Loyalitas Pelanggan Pada Chanel Distro Di Tenggarong - Sadiyah, Halimatus; Palinggi, Yonathan; Adawiyah, Raudatul (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract :The aim of this research is to know whether Pshycal Evidance and Life Style Influence Simultaneously on Customer Loyalty In Chanel Distro In Tenggarong, to know whether Pshycal Evidance And Lifestyle Affects Partially To Customer Loyalty In Chanel Distro In Tenggarong and to know from both variables, which is the most dominant influence Customer Loyalty In Chanel Distro In Tenggarong. In the data analysis, in accordance with the object of research to determine the magnitude of the influence of Pshycal Evidance And Lifestyle to customer loyalty is with the model of multiple regression analysis with the help of SPSS For Window 20.0. Result of calculation of test of F (simultaneous correlation / together), obtained F count bigger than F table (Fhitung 25,227> Ftabel 3,13), so it can be said physical evidence variable and lifestyle simultaneously (able to show its effect on customer loyalty. Then the first hypothesis that